Winning the math wars : no teacher left behind - Abbott, Martin, 1949- (Washington School Research Center in association with University of Washington Press, 2010)
"In this volume, four scholars at the Washington School Research Center at Seattle Pacific University present original research drawn from statistical studies of state educational data and from thousands of classroom observations. They assess the current state of math education and review its history and development."--[book cover]